Non‐canonical autophagy functions of ATG16L1 in epithelial cells limit lethal infection by influenza A virus. (15th February 2021) - Wang, Yingxue; Sharma, Parul; Jefferson, Matthew; Zhang, Weijiao; Bone, Ben; Kipar, Anja; Bitto, David; Coombes, Janine L; Pearson, Timothy; Man, Angela; Zhekova, Alex; Bao, Yongping; et al.
Abstract: Influenza A virus (IAV) and SARS‐CoV‐2 (COVID‐19) cause pandemic infections where cytokine storm syndrome and lung inflammation lead to high mortality. Given the high social and economic cost of respiratory viruses, there is an urgent need to understand how the airways defend against virus infection. Here we use mice lacking the WD and linker domains of ATG16L1 to demonstrate that ATG16L1‐dependent targeting of LC3 to single‐membrane, non‐autophagosome compartments – referred to as non‐canonical autophagy – protects mice from lethal IAV infection. Mice with systemic loss of non‐canonical autophagy are exquisitely sensitive to low‐pathogenicity IAV where extensive viral replication throughout the lungs, coupled with cytokine amplification mediated by plasmacytoid dendritic cells, leads to fulminant pneumonia, lung inflammation and high mortality. IAV was controlled within epithelial barriers where non‐canonical autophagy reduced IAV fusion with endosomes and activation of interferon signalling. Conditional mouse models and ex vivo analysis showed that protection against IAV infection of lung was independent of phagocytes and other leucocytes. This establishes non‐canonical autophagy in airway epithelial cells as a novel innate defence that restricts IAV infection and lethal inflammation at respiratory surfaces. SYNOPSIS: Non‐canonical functions of the autophagy protein ATG16L1 are mediated by its C‐terminal WD domain. Here, mice expressing WD domain‐lacking ATG16L1 are found to be highly sensitive to influenza virus infection, resulting in cytokine storm and lethal pneumonia. The WD domain of ATG16L1 prevents lethal infection by influenza A virus. Infection is controlled by epithelial cells and is independent of phagocytic cells. Non‐canonical ATG16L1 function reduces interferon signalling by slowing virus endocytosis and fusion with endosomal membranes. Abstract : Deletion of WD domain mediating non‐canonical functions of ATG16L1 sensitizes mice to cytokine storm and lethal pneumonia upon influenza infection.